Exploitation of quarries in hill Arunta and its influence on the degradation of the natural landscape of Tacna in the year 2016. - Martinez Valdivia, Ana Noelia (2017)
Objective: To demonstrate how the presence of the surface exploitation of quarries has influenced the degradation of the natural landscape of Arunta hill in the Gregorio Alba rracín Lanchipa district of Tacna. Method: The research will be of the basic type; the research design is descriptive and explanatory, being therefore a non-experimental investigation. Results: The main results show that the modification of the physiographydiminishes the visual quality, whereas the natural systems begin to have problems derived from the decrease of habitat surface, due to the fragmentation and environmental fragility. Conclusions: it is a contribution to new investigations of diverse specialties, since it has been verified that the sector has a correctable degradation of the natural landscape, being landscape subject a tool of management.